Analysis of interroom quality control of syphilis test in Shaoguan city of Guangdong province in 2018 - Shang-hua WU; Lan WANG; Ying CHEN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2019)
Objective: To improve the level of syphilis serology test in the laboratory of medical institutions for the treatment of venereal diseases in Shaoguan city of Guangdong province by evaluating the serological quality of syphilis, and to analyze the choice of serological test methods and the accuracy of testing methods of various laboratories. Methods: One hundred and forty-two laboratories of medical institutions in Shaoguan city for the treatment of sexually transmitted diseases were selected, and the diagnostic technique and quality control training courses for sexually transmitted diseases were held in 2018. Each laboratory distributed five syphilis serological quality control products. The examination content included three kinds of test items: qualitative and quantitative test of non-specific antibodies of syphilis, and qualitative test of syphilis specific antibodies. The laboratoies were required to conduct tests within a specified time and report the results through the network. Results: Of the 39 sexually transmitted diseases laboratories passed the evaluation of the sexually transmitted diseases laboratory, 34 had excellent quality evaluation(≥90 points) accounting for 87.18%; 5 good(75~<90 points) accounting for 12.82%. The pass rate of the 39 non-syphilis spiral serolog (NTT) and syphilis spiral serology(TT) laboratories assessed for sexually transmitted diseases was both 100%, and the compliance rate of dection method was 100%, 97.14%, respectively. Of 103 laboratories failed the evaluation, 63 participated in NTT, the assessment rate was 57.14%, and the compliance rate of dection method was 53.97%. 69 laboratories participated in the TT assessment, with a assessment rate of 53.62% and a compliance rate of 73.91%. The assessment rate (χ2=22.73、21.60, both P<0.01) and the compliance rate (χ2=376.26、142.65, both P<0.01) of NTT quantitative test and TT quantitative in the laboratories passed the evaluation were significantly higher than that in laboratories failed the evaluation. Conclusion: The results of the assessment of interroom quality of venereal disease laboratory in Shaoguan city in 2018 are superior to those of laboratories that have not passed the evaluation and there are many problems in those laboratories. It is necessary to pay attention to strengthen the quality management of syphilis test and improve the level of testing.